3D free‐breathing cardiac magnetic resonance fingerprinting. (21st July 2020) - Cruz, Gastão; Jaubert, Olivier; Qi, Haikun; Bustin, Aurélien; Milotta, Giorgia; Schneider, Torben; Koken, Peter; Doneva, Mariya; Botnar, René M.; Prieto, Claudia
Abstract : Purpose: To develop a novel respiratory motion compensated three‐dimensional (3D) cardiac magnetic resonance fingerprinting (cMRF) approach for whole‐heart myocardial T 1 and T 2 mapping from a free‐breathing scan. Methods: Two‐dimensional (2D) cMRF has been recently proposed for simultaneous, co‐registered T 1 and T 2 mapping from a breath‐hold scan; however, coverage is limited. Here we propose a novel respiratory motion compensated 3D cMRF approach for whole‐heart myocardial T 1 and T 2 tissue characterization from a free‐breathing scan. Variable inversion recovery and T 2 preparation modules are used for parametric encoding, respiratory bellows driven localized autofocus is proposed for beat‐to‐beat translation motion correction and a subspace regularized reconstruction is employed to accelerate the scan. The proposed 3D cMRF approach was evaluated in a standardized T 1 / T 2 phantom in comparison with reference spin echo values and in 10 healthy subjects in comparison with standard 2D MOLLI, SASHA and T 2 ‐GraSE mapping techniques at 1.5 T. Results: 3D cMRF T 1 and T 2 measurements were generally in good agreement with reference spin echo values in the phantom experiments, with relative errors of 2.9% and 3.8% for T 1 and T 2 ( T 2 < 100 ms), respectively. in vivo left ventricle (LV) myocardial T 1 values were 1054 ± 19 ms for MOLLI, 1146 ± 20 ms for SASHA and 1093 ± 24 ms for the proposed 3D cMRF; corresponding T 2 values were 51.8 ± 1.6 ms for T2‐GraSE and 44.6 ± 2.0 ms for 3D cMRF. LV coefficients of variation were 7.6 ± 1.6% for MOLLI, 12.1 ± 2.7% for SASHA and 5.8 ± 0.8% for 3D cMRF T 1, and 10.5 ± 1.4% for T2‐GraSE and 11.7 ± 1.6% for 3D cMRF T 2 . Conclusion: The proposed 3D cMRF can provide whole‐heart, simultaneous and co‐registered T 1 and T 2 maps with accuracy and precision comparable to those of clinical standards in a single free‐breathing scan of about 7 min. Abstract : A method for free‐breathing 3D cardiac Magnetic Resonance Fingerprinting (cMRF) is developed for simultaneous, co‐registered, whole‐heart T1/T2 mapping. The proposed approach combines variable magnetization preparation for T1/T2 encoding, localized autofocus for respiratory motion correction and subspace regularized reconstruction for aliasing reduction, providing parametric maps in a single free‐breathing scan of 7 min.